Trends in Modern Contraceptive Use among Young Adult Women in sub‐Saharan Africa 1990 to 2014. Issue 4 (15th November 2018) - Behrman, Julia Andrea; Wright, Kelsey Quinn; Grant, Monica J.; Soler‐Hampejsek, Erica
Abstract: This article provides updated estimates of trends in modern contraceptive use among young adult women (aged 15–24) who have had sex, using Demographic and Health Survey data from 23 sub‐Saharan African countries (1990–2014). In East/South Africa, parous women had higher modern contraceptive use than nulliparous women and larger increases in modern contraceptive use over time. In the West/Central region, nulliparous women had higher modern contraceptive use than parous women and larger increases in modern contraceptive use over time. Most of the increase in modern contraceptive use was driven by an increase in short‐acting—rather than long‐acting—methods across regions and parity groups. Although parous women had higher unmet need for family planning in both regions, nulliparous women had larger increases in unmet need for family planning over time in the East/South region. Decomposition analysis suggests that increases in use of modern contraceptives are largely driven by increases in the rate of contraceptive use rather than changes in the parity composition of women.